(untitled) - Kavis, Michael
Includes bibliographical references and index; An expert guide to selecting the right cloud service model for your business Cloud computing is all the rage, allowing for the delivery of computing and storage capacity to a diverse community of end-recipients. However, before you can decide on a cloud model, you need to determine what the ideal cloud service model is for your business. Helping you cut through all the haze, Architecting the Cloud is vendor neutral and guides you in making one of the most critical technology decisions that you will face
Keywords: Information technology -- Management; Cloud computing; Computer architecture; Công nghệ thông tin -- Quản lý; Điện toán đám mây; Kiến trúc máy tính